2019
DOI: 10.1136/bjophthalmol-2018-313461
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of optical coherence tomography angiography in glaucoma: a systematic review and meta-analysis

Abstract: BackgroundCompared with current imaging methods, the diagnostic performance and the advantages and limitations of optical coherence tomography angiography (OCTA) remain unclear. We performed a systematic review and meta-analysis of studies investigating vessel density (VD) in patients with glaucoma using OCTA.MethodsWe conducted a literature search on PubMed, Scopus, Web of Science, ISI Conference Proceedings and Google Scholar, along with a manual search, from January 2006 to March 2018. We included prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…A comprehensive search was performed using four electronic databases from inception to September 20 th 2019 -MEDLINE, Scopus, ISI Web of Science, and Google Furthermore, through grey literature, unpublished data, and a hand search of references of the included studies and reviews, additional studies were identified. The review protocol was registered 26 on PROSPERO (record number CRD42020153576).…”
Section: Search Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…A comprehensive search was performed using four electronic databases from inception to September 20 th 2019 -MEDLINE, Scopus, ISI Web of Science, and Google Furthermore, through grey literature, unpublished data, and a hand search of references of the included studies and reviews, additional studies were identified. The review protocol was registered 26 on PROSPERO (record number CRD42020153576).…”
Section: Search Strategymentioning
confidence: 99%
“…16 Third, OCTA may provide information on the vascular pathophysiology of glaucoma. 17 Previous studies, including a meta-analysis 18 , have shown that OCTA can be useful for glaucoma diagnosis. 19 More recently, studies have evaluated the ability of OCTA to detect and measure glaucoma progression.…”
Section: Introductionmentioning
confidence: 99%
“…found a significant reduction in mean circumpapillary vessel density reported in glaucomatous eyes for many OCTa devices. [ 20 ] Moghimi et al . were able to show a correlation between vessel density and visual field MD, even in advanced glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…107,108 Other chronic eye diseases such as glaucoma or age-related macular degeneration may also impact the results of OCT/OCTA findings. [109][110][111] In addition, certain OCT/OCTA findings such as FAZ size can vary by age, race, or sex, 112,113 and can vary substantially between individuals thus limiting its utility. Moreover, if these factors are not controlled for in the analysis, then the relationship between FAZ and AD or MCI can be confounded.…”
Section: Dovepressmentioning
confidence: 99%